Quantitative Proteome Analysis Reveals Changes in the Protein Landscape During Grape Berry Development With a Focus on Vacuolar Transport Proteins - Kuang, Liuqing; Chen, Shangwu; Guo, Yan; Ma, Huiqin (Frontiers in Plant Science, 2019)
The vacuole plays a central role in fruit growth and quality formation, yet its proteomic landscape is largely unknown. In the present study, a protocol for isolating intact vacuoles from grape flesh tissue was successfully established. Quantitative proteome analysis identified 2533 proteins from five sampling dates along Cabernet Sauvignon berry development from stage I to III; among them, 1443 proteins were identified on all five sampling dates in at least two biological replicates per sample and were designated core proteome, and 1820 were recruited as differentially abundant proteins (DAPs) by sequential pairwise comparisons using arbitrary fold change of >1.5 and P < 0.05. Metabolism consistently constituted the largest category of identified proteins for both core proteome and DAPs, together with a consistently high proportion of protein-fate category proteins, indicating that the classic lytic functions of vegetative cell vacuoles are maintained throughout berry development; accumulation of metabolites involved in high sugar and other berry qualities in the late developmental stage added to the conventional lytic role of the flesh cell vacuoles. Overall increases in abundance of the DAPs were seen in the transporter proteins, membrane fusion/vesicle trafficking, and protein-fate categories, and decreased abundance was seen for DAPs in the stress, energy and cytoskeleton categories as berry development progressed. A very pronounced proteomic change was revealed between late stage I and mid stage II, with 915 increased and 114 decreased DAPs, demonstrating a significant surge of the vacuolar proteome underlying the rather static phenotypical and physiological phase. We identified 161 transport proteins with differential abundance, including proton pumps, aquaporins, sugar transporters, ATP-binding cassette transporters and ion transport proteins, together with organic compound transport proteins, the highest number and variety of berry tonoplast transporters found in grape proteome efforts to date. We further found a pre-positive increment of 96 transport proteins from the middle of stage II, before the berry undergoes its dramatic physiological changes at and following véraison. Our results are the first to describe the proteome of a vacuole-enriched preparation, toward understanding the functions of the largest compartment in berry cells during grape growth and ripening.